The Effect of Steamed Raja Banana on Reducing Dysmenorrhea Intensity among Adolescent Girls at Cinta Youth Posyandu, Pegiringan Village, Bantarbolang Sub-district, Pemalang Regency - Widya Agita Astiani; Khamidah Achyar (Proceedings Series on Health & Medical Sciences, 2026)
Dysmenorrhea is a common reproductive health problem among adolescent girls that may interfere with daily activities and reduce quality of life. Non-pharmacological therapy such as consuming potassium-rich foods, including steamed Raja banana, may help reduce menstrual pain. Dysmenorrhea is a common reproductive health problem among adolescent girls that may interfere with daily activities and reduce quality of life. Non-pharmacological therapy such as consuming potassium-rich foods, including steamed Raja banana, may help reduce menstrual pain. The proportion of moderate pain decreased from 22 respondents (64.71%) to 5 respondents (14.71%), and severe pain decreased from 5 respondents (14.71%) to 2 respondents (5.88%). Meanwhile, respondents reporting no pain increased from 0 to 12 (35.29%). The Wilcoxon test showed a significant reduction in dysmenorrhea intensity (p = 0.000; p < 0.05). Steamed Raja banana significantly reduces dysmenorrhea intensity among adolescent girls.